Metal–Organic Frameworks: Boosting Catalysis of Pd Nanoparticles in MOFs by Pore Wall Engineering: The Roles of Electron Transfer and Adsorption Energy (Adv. Mater. 30/2020). Issue 30 (28th July 2020) - Chen, Dongxiao; Yang, Weijie; Jiao, Long; Li, Luyan; Yu, Shu‐Hong; Jiang, Hai‐Long
Abstract : The isoreticular metal–organic framework (MOF) UiO‐66‐X with diverse functional groups, encapsulating guest Pd nanoparticles, is fabricated by H.‐L. Jiang and co‐workers, as described in article number 2000041 . The chemical microenvironment around the Pd is systematically regulated by these MOF hosts, giving rise to distinctly different performances toward the hydrogenation of benzoic acid.